RAHASIA MEWUJUDKAN INDIVIDU DAN MASYARAKAT YANG SEHAT BERBASIS SPIRITUALITAS AGAMA HINDU - Atmadja, Nengah Bawa; Ariyani, Luh Putu Sri (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2025)
Pura Negara Gambur Anglayang is an important and unique temple, so many people are interested in studying it. This article results from field research on the Pura Kerta Negara Gambur Anglayang in the Kubuaddan Traditional Village, Buleleng, Bali. This research aims to reveal the background of using the names Ratu Subandar, Mecca, Melayu, and Sundawan as names for the shrines or pelinggih at the temple. This research uses a qualitative approach in the form of historical and cultural research. The theoretical approach used is cultural materialism. The research results show that the use of the names Ratu Subandar, Mecca, Melayu, and Sudawan is related to the location of the temple, which was previously a port called Tabanding. This port was busy with Chinese, Mecca (Arab), Malay and Sundanese traders. The Chinese also played an important role as subandars. The diversity of merchant visits gave rise to a multicultural social structure based on trade-economic infrastructure. This forms an ideological superstructure, namely the belief in gods, also characterised by diversity. This pattern also follows pantheistic theology in Hinduism, which emphasises that a transcendental God can be immanenced by natural phenomena. This belief causes natural phenomena that have the potential to provide prosperity to be personified by gods. The Balinese accept it because it also fits the image of the god as the personification of God to provide prosperity to humans.